Efficient defense strategy against spam and phishing email: An evolutionary game model. (September 2021) - Wang, Mengli; Song, Lipeng
Abstract: Spam and phishing emails are never-ending problems, and they are increasingly distributed with the help of the botnet. Existing spam and phishing email defense depends heavily on the spam filtering technique. However, using the spam filtering technique needs many defensive resources, which are usually limited. Therefore, to achieve the maximum effect with limited defense resources, we answer the following questions in this paper: How many user nodes we should protect in a target network? What factors affect this and how? To solve these problems, we propose an evolutional game model between multiple attackers and multiple defenders and analyze the evolution process of their strategies. The optimal number of users protected is first obtained as an efficient defense strategy, which can reduce resource consumption and lower attack density. Then we discover that this defense strategy is affected by the email opening probability of users, the attack cost, and the attack loss. Our results can help email network managers deploy the spam filtering technique according to the email opening probability, of which the defender has an asymmetric information advantage. Furthermore, we study the influences of the attack cost and loss on the defense strategy. It is revealed that the attack cost has a more marked effect on the defense strategy compared to the attack loss. Finally, we experiment on a large real-world dataset of emails sent in 2-year time duration. The defense strategy is proven to be effective for maximizing defense resources.